Endovascular Treatment of Blood Blister-Like Aneurysms Using Multiple Self-Expanding Stents - Kim, Young Woo (The Korean Neurosurgical Society, 2011)
The surgical as well as endovascular treatment of blood-blister-like aneursysms (BBAs) is extremely difficult because of these pathological natures, such as small and the fragile necks. The optimal treatment of BBAs has remained uncertain. Stents are known to divert blood flow and induce thrombosis of intracranial aneurysms. We report 3 cases of successful obliteration of BBAs after multiple stents placement.